Impairment of peroxisomal structure and function in rat liver allograft rejectiond: prevention by cyclosporine - Steinmetz, Irmtraud; Weber, Thomas; Beier, Konstantin; Czerny, Franz; Kusterer, Klaus; Hanisch, Ernst; Völkl, Alfred; Fahimi, H. Dariush; Angermüller, Sabine (Transplantation, 1998)
Background. - During allograft rejection, cytokines and lipid mediators contribute to cell injury and organ failure. Peroxisomes play a crucial role in lipid metabolism, including the degradation of lipid mediators by peroxisomalβ-oxidation. Therefore, we investigated the alterations of hepatic peroxisomes after allogeneic rat liver transplantation. - Methods. - MHC-incompatible Dark Agouti (RT1a) donor rats and Lewis(RT11) recipient rats were used for allogeneic transplantation. For immunosuppression, a group of these animals received cyclosporine (CsA) intraperitoneally (1 mg/kg body weight per day). Lewis rats were used for isogeneic transplant combination. Ten days after transplantation, livers were investigated using morphometrical methods for determination of peroxisomal diameter and volume density. The activities of peroxisomal catalase (CAT) and acylcoenzyme A oxidase (AOX) were determined, and the corresponding proteins were evaluated by quantitative immunocytochemistry and immunoblotting. The expressions of mRNAs encoding CAT and AOX were investigated by Northern blotting. - Results. - The volume density and diameter of peroxisomes were significantly decreased in allogeneic transplanted livers but were unchanged in CsA-treated animals. Both the activities of CAT and AOX and their protein levels were significantly reduced in liver allografts. Moreover, the corresponding mRNA levels of CAT and AOX were decreased significantly in liver allografts, whereas CsA treatment led to an increase of those mRNAs. Isogeneic transplanted livers showed only a slight reduction of the corresponding enzyme values. - Conclusions. - Peroxisomes are severely affected both morphologically and functionally after allogeneic liver transplantation. These results suggest that impairment of peroxisomal lipid βoxidation could contribute to the pathogenesis of the rejection process by decreased catabolism of lipid mediators involved in the regulation of the inflammatory response. CsA, in addition to its immunosuppressive effects, may contribute to allograft survival by maintenance of those important peroxisomal functions.